Perlindungan Hukum Terhadap Hak Asasi Manusia Dalam Hukum Tata Negara - Kuswan Hadji; Devina Angelica; Efi Lailatun Nisfah; Erlingga Savril Maharani; Herfita Ayu Nayla; Clara Oktaviana (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Human rights are fundamental rights inherent in every individual without exception, which must be respected, protected, and fulfilled by the government in accordance with the principles of applicable constitutional law. This study aims to analyze the legal protection of human rights in the context of constitutional law. The research method used is a descriptive analytical approach that discusses the concept of human rights, its relation to constitutional law, as well as concrete steps that can be taken by the government to ensure effective human rights protection. The results showed that legal protection of human rights in constitutional law is very important to maintain a balance between state power and individual rights. A balance between individual freedom and public interest is needed in carrying out government duties in accordance with the constitution and applicable laws and regulations. This research is expected to provide deeper insight into efforts to protect human rights within the framework of constitutional law, and can be a reference for governments, legislative institutions, and law enforcement agencies in improving human rights protection as one of the key aspects in realizing a democratic and just rule of law.